Fixed dosing of kukoamine B in sepsis patients: Results from population pharmacokinetic modelling and simulation. Issue 9 (23rd April 2022) - Wang, Huanhuan; Wang, Teng; Hu, Xiaoyun; Deng, Chenhui; Jiang, Ji; Qin, Hanyu; Dong, Kai; Chen, Shuai; Jin, Chunyan; Zhao, Qian; Du, Bin; Hu, Pei
Abstract : Aims: To assess the appropriateness of the body weight or fixed dosing regimen, a population pharmacokinetic (PopPK) model of kukoamine B has been built in sepsis patients. Methods: Plasma concentrations of kukoamine B and the covariates information were taken from 30 sepsis patients assigned into 0.06 mg/kg, 0.12 mg/kg and 0.24 mg/kg groups in a Phase IIa clinical trial. The PopPK model was built using a nonlinear mixed‐effect (NLME) modelling approach. Based on the final model, PK profiles were respectively simulated 500 times applying the body weight and renal function information of 12 sepsis patients from the 0.24 mg/kg group on the body weight or the fixed dosing regimen. For each dosing regimen, PK profiles of 6000 virtual patients were obtained. Statistical analyses for C max and C min were performed. If the biases of C max and C min can all meet the criteria of ±15%, the fixed dosing regimen can substitute for the body weight dosing regimen. Results: The PopPK model was successfully developed using the NLME approach. A bi‐compartmental model was selected as the basic model. Renal function was identified as a statistically significant covariate of systemic clearance with the objective function value (OFV) decreasing 8.6, resulting in a 5.2% decrease in inter‐individual variability (IIV) of systemic clearance. Body weight was not identified as a statistically significant covariate. Simulation results demonstrated two methods had a bias of 8.1% for C max, and 8.6% for C min . Furthermore, PK variability was lower on the fixed dosing regimen than the body weight regimen. Conclusions: Based on the simulation results, a fixed dosing regimen was recommended in the subsequent clinical trials.